Robust large-gap topological insulator phase in transition-metal chalcogenide ZrTe4Se. (30th September 2021) - Wang, Xing; Wan, Wenhui; Ge, Yanfeng; Liu, Yong
Abstract: Based on density functional theory, we investigate the electronic properties of bulk and single-layer ZrTe4 Se. The band structure of bulk ZrTe4 Se can produce a semimetal-to-topological insulator (TI) phase transition under uniaxial strain. The maximum global band gap is 0.189 eV at the 7% tensile strain. Meanwhile, the Z 2 invariants (0; 110) demonstrate conclusively it is a weak topological insulator. The two Dirac cones for the (001) surface further confirm the nontrivial topological nature. The single-layer ZrTe4 Se is a quantum spin Hall insulator with a band gap 86.4 meV and Z 2 = 1, the nontrivial metallic edge states further confirm the nontrivial topological nature. The maximum global band gap is 0.211 eV at 8% uniaxial tensile strain along the [100] direction. When the compressive strain is more than 1%, the band structure of single-layer ZrTe4 Se produces a TI-to-semimetal transition. These theoretical analysis may provide a method for searching large band gap TIs and platform for topological nanoelectronic device applications. Video Abstract: Video Abstract: Robust large-gap topological insulator phase in transition-metal chalcogenide ZrTe4 Se